A Clatter of Jars - Graff, Lisa 1981- (Lisa Colleen) (New York, NY : Philomel Books, 2016)
"Children with magical Talents attend a summer camp, where nothing is what it seems"--
Keywords: Magic -- Juvenile fiction; Camps -- Juvenile fiction; Fantasy; Magic -- Fiction; Camps -- Fiction; JUVENILE FICTION / Social Issues / Friendship; JUVENILE FICTION / Family / Siblings; JUVENILE FICTION / Fantasy & Magic